Effect of Coarse Aggregate Dimensional Variation On The Compressive Strength of Concrete - Yogika Oktavian; Hafiz Hamdani; Adryan Fitrayudha (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
In the world of construction, concrete has a very important function as the main material due to its role in maintaining the strength and stability of the structure. This study aims to evaluate the effect of coarse aggregate size variations on the compressive strength of concrete and determine the most suitable size for use. The use of coarse aggregates is focused on granules that are retained on 3/4-inch and 3/8-inch sieves. The results showed that concrete with coarse aggregate retained in a 3/8 inch sieve had a higher compressive strength than 3/4 inch aggregate. At 3 days of age, the average compressive strength value reached 12,078 MPa for 3/8 inch coarse aggregate and 10,587 MPa for 3/4 inch aggregate. This difference continued at the 28-day lifetime compressive strength (the result of the 1971 PBI conversion), which was with an average value of 30,296 MPa for a 3/8 inch aggregate and 26,469 MPa for a 3/4 inch aggregate. This difference is due to a tighter distribution of patricles, reduced pore volume, and more optimal bonding of cement paste and aggregate. Therefore, the selection of coarse aggregate sizes needs to be adjusted to the purpose of construction.